Initial Impact of the COVID-19 Pandemic on Physician Assistant Education. Issue 2 (June 2022) - Valentin, Virginia; Najmabadi, Shahpar; Warner, Mary; White, Ryan; Dehn, Richard
Abstract : Purpose: The COVID-19 pandemic significantly impacted United States (US) health professions educational programs. Physician assistant (PA) programs were forced to respond to rapidly changing circumstances early in the pandemic. This study describes the impact that the early phase of the COVID-19 pandemic had on PA programs in the United States. Methods: This cross-sectional study is based on data from the COVID-19 Rapid Response Report 1, conducted by the Physician Assistant Education Association in April 2020. The survey sample included 254 US PA program directors with a response rate of 64.2%. Our outcome measures included temporary changes to PA program operations and clinical training, and current and upcoming budget and tuition changes, as well as the impact of the pandemic on faculty and staff employment. We used descriptive statistics to summarize these outcomes, stratified by 4 categories characterizing features of PA programs, including geographical location, academic housing, funding model, and academic health center status. Results: The COVID-19 pandemic impact on programs varied geographically. A majority of programs reported making numerous temporary changes to their operations. Most programs moved both didactic and clinical education to an online format. Clinical training was temporarily suspended at almost all programs. Conclusions: PA programs continued training despite the pandemic. The long-term impact of the pandemic may be the instability of the PA education workforce.